Pusat Hasil Laut Dengan Pendekatan Arsitektur Neo-Vernakular Di Kabupaten Wakatobi - Nahdatunnisa, Nahdatunnisa; Sari Taufiq, Elvina; Hairun, Ahmad (Architectura : Journal of Architecture and Planning, 2025)
Wakatobi Regency has abundant seafood potential, but its utilization is still not optimal due to the lack of processing and distribution infrastructure. Therefore, a Seafood Center is needed that not only functions as a place for processing and marketing, but also as an education and research center. The main objective of this design is to create facilities that support the sustainability of the fishing industry and strengthen local cultural identity. The methods used in the design include literature study, site analysis, and Neo-Vernacular architectural approach, which adapts traditional elements of Wakatobi with modern technology and materials. The design results show that the application of the Neo-Vernacular concept can create a building that is in harmony with the environment, functional, and useful for the community. In conclusion, the Seafood Center is expected to improve local economic welfare and maintain the sustainability of marine resources in Wakatobi.